Kościół jako ikona Ciała Chrystusa w Pierwszym Liście do Koryntian - Adamczewski, Bartosz (Verbum Vitae, 2004)
Pauls imagery of the Body of Christ as a description of the Church differs from its plausible hellenistic parallels, among other things, in bringing into prominence the weaker, shameful members of the Body (1 Cor 12:22-24). They are considered necessary for the Body not primarily because of the importance of their function for the whole, but because of their particular role in revealing the paradox of Christs weakness leading to glory (cf. 1 Cor 1-4).The Church can be, therefore, considered not only the place of Christs salvific presence and activity, but also an icon of the Body of Christ: crucified and glorified. This christomorphic image should be recognized and enacted by the Church herself particularly in celebrating the liturgy of the Eucharist.